Embracing Ramadhan with FELDA / E. Tavasuria Ekangovan - Ekangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
May 26, 2018, 'ASET Ramadhan bersama masyarakat FELDA' programme was organized by UiTM Perak Branch, Tapah Campus at Felda Gunung Besout 3. A total number of 45 students, 6 FSG lecturers and 1 FSG staff from the Faculty of Applied Science (FSG) were involved in this programme. The aim of the programme is to create teamwork between students that will help them to be more open minded and creative when interacting with the FELDA residents.